Bridging Language Learning and Entrepreneurship: Examining Arabic Language Students’ Potential in Developing 'Arabic for Specific Purposes' Module Projects - Muslimah, Maziyyatul; Afyuddin, Moh Sholeh; Cahyono, Machrup Eko; Pradana, Satria Adi (Institut Agama Islam Negeri Palangka Raya, 2025)
This research explores the potential of Arabic language students in Indonesia to develop